Effects of an ambient odor on brain activations during episodic retrieval of objects. - Galliot, Emmanuel; Comte, Alexandre; Magnin, Eloi; Tatu, Laurent; Moulin, Thierry; Millot, Jean-Louis (Brain Imaging & Behavior, 2013)
This study investigated the brain areas involved in episodic memory retrieval of pictures depending on the characteristics of the contextual environment during encoding (i.e. presence or absence of an odor). In the first stage, subjects were presented with a series of 32 pictures. Half of the pictures were presented while the subjects smelled an odor (vanillin). No particular odor was associated with the presentation of the other half of the pictures. Two weeks later, a retrieval task was performed in which the same pictures were presented during an fMRI session but without any odor association involved. The results show that both conditions activate a common episodic memory network including the hippocampal formation. Compared with the "encoding without odor" condition, the "encoding with odor" condition shows greater activations in temporal, parietal and frontal cortices, notably within the area of the orbitofrontal cortex which constitutes a main site of the secondary olfactory cortex. No activated areas were observed in the inverse contrast. These results highlight the complexity of the networks involved in episodic memory according to the context during encoding.